Factor analysis of waste management in Serang Regency, Indonesia - Harsanto, Cahyo; Kadar, Isman; Istiadi, Yossa (Universitas Pakuan, 2024)
Serang Regency, with an area of 1,467.35 km2 in 2020 had a population of 1,622,630 people. By referring to SNI 19-3983-1995, the waste capacity produced on average is 2.25 liters per person per day, so the potential waste in Serang Regency in 2020 is around 1,212,903.7 m3 /year, while the amount of waste that can be transported to the final waste processing site (or TPA) is 98,339 m3 . Based on this data, waste services in Serang Regency have only reached 7.37%, far from the target of the Serang District Regional Policy and Strategy (Jakstrada) of 74% as stated in the Serang Regency Regulation No. 6 of 2021. On the other hand, there are still many roadside piles of waste in Serang Regency, which indicates that there is still a lack of community participation in waste management. Waste management involves several factors, including institutions or organizations, laws, regulations, management financing, technical and operational waste, as well as community attention and participation. Looking at the phenomenon, analysis of waste management factors in Serang Regency was carried out so that the dominant factors in improving waste management performance could be identified for further planning of strategies to optimize waste management, both through waste handling and waste reduction. Based on the analysis carried out using SPSS, it can be stated that factors of operational technical, organizational, legal, and regulatory, as well as factors of financing and community participation are suitable to be used as a policy combination to improve waste management performance in Serang Regency.